Library System Development Using Design Thinking Method - Levina Dewi, Grace; Tjandra, Suhatati; Cahyani Styoningrum, Indah; Ardhi, Setya (Publisher Cv. Inara, 2024)
The library information system that is currently being used is still inadequate in providing information and various problems occur on the website which disrupt various transaction activities in the library. The aim of creating this website is to provide facilities for all users, from librarian, and students to lecturers, to obtain library information easily. The website will be built with various features in the hope of making it easier for users to get information from the library. Using the design thinking method, research is carried out to identify problems that occur and solutions are found according to the needs of library users. Based on the results of the usability test, the score was above average and in the good category and this system can be generally accepted by all users. Even though the usability results were unsatisfactory, the majority of users, 82.41%, were satisfied with this library system. The performance test results also show that the website has very good performance with an average score of 92.68%.